If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -4 = 8(x + -5) Reorder the terms: -4 + 7x = 8(x + -5) Reorder the terms: -4 + 7x = 8(-5 + x) -4 + 7x = (-5 * 8 + x * 8) -4 + 7x = (-40 + 8x) Solving -4 + 7x = -40 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -4 + 7x + -8x = -40 + 8x + -8x Combine like terms: 7x + -8x = -1x -4 + -1x = -40 + 8x + -8x Combine like terms: 8x + -8x = 0 -4 + -1x = -40 + 0 -4 + -1x = -40 Add '4' to each side of the equation. -4 + 4 + -1x = -40 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = -40 + 4 -1x = -40 + 4 Combine like terms: -40 + 4 = -36 -1x = -36 Divide each side by '-1'. x = 36 Simplifying x = 36
| -3(x+2)-6=2(x-4)+8 | | 3x+x+2/3x=23 | | a+11/4=27/10 | | 4/3+8/x | | -7/8=2/3+n | | 48/300 | | 4x-3x=3+3x-3x | | 12=2l+4 | | 44-3x=6x+15 | | -10(-9x+10)=-550 | | 6k-3(1-2k)=33 | | -x+9=x-45 | | 8-(g+7)=21 | | 6(7x+10)=564 | | n+22=38 | | -7(8x+2)=378 | | -(m-11)=13 | | 100=-(x+8)+2x | | 3(2z-3)=5(z+2) | | 2(9x)+2(2x)=484 | | 7(5x+13)=301 | | 2/3x=-1/2 | | 3w+4+2w=-26 | | (1)/(5p2)*(5p3-35p2)/(9p-36) | | X(2)+2x=23 | | 5x+2=9x-22 | | w/7+2=5 | | 5(-9x+15)=-195 | | x=450-.5y | | 3k+16=5 | | 7x^-3/16x^-1 | | 5(-9+15)=-195 |